Pengaruh Harga Produk Terhadap Keputusan Pembelian (Survey Pada Konsumen Toserba Yogya Gatot Subroto) - Elin Nurfitriani; Dede R. Oktini (UNISBA Press, 2022)
Abstract. This study aims to determine the application of prices carried out by the Yogya Gatot Subroto Department Store, to find out respondents' responses to the prices at the Yogya Gatot Subroto Department Store, to find out respondents' responses to purchasing decisions at the Yogya Gatot Subroto Department Store, and to find out how much influence the price has on purchasing decisions at the Yogya Gatot Subroto Department Store. Yogyakarta Gatot Subroto department store. This research is included in quantitative research with descriptive and verification types of research. The research method used is a survey method with a sampling technique using nonprobability sampling with the type of sampling used incidental sampling, then obtained a sample of 100 people from the existing population. The population in this study were consumers of the Yogya Gatot Subroto department store in Bandung. The data analysis method in this study uses simple linear regression analysis with the aim of knowing the direction of the relationship between the independent variable (X) and the dependent variable (Y). Pricing at the Yogya Gatot Subroto Department Store in Bandung can be said to be quite good. Respondents' responses regarding prices at the Yogya Gatot Subroto Department Store Bandung are in the sufficient category. Respondents' responses regarding purchasing decisions at the Yogya Gatot Subroto Department Store Bandung are in the sufficient category. The data is normally distributed and does not experience heteroscedasticity. The results of this study indicate that there is a partial influence between the price variables on purchasing decisions. Keywords: Price, Purchase Decision Abstrak. Penelitian ini bertujuan untuk mengetahui penerapan harga yang dilakukan Toserba Yogya Gatot Subroto, untuk mengetahui tanggapan responden mengenai harga di Toserba Yogya Gatot Subroto, untuk mengetahui tanggapan responden mengenai keputusan pembelian di Toserba Yogya Gatot Subroto, serta untuk mencari seberapa besar pengaruh harga terhadap keputusan pembelian di Toserba Yogya Gatot Subroto. Penelitian ini termasuk kedalam penelitian kuantitatif dengan jenis penelitian deskriptif dan verifikatif. Metode penelitian yang digunakan adalah dengan metode survey dengan teknik penarikan sampel menggunakan nonprobability sampling dengan jenis sampling yang digunakan yaitu sampling insidental, kemudian didapat sampel sebanyak 100 orang dari populasi yang ada. Populasi dalam penelitian ini adalah konsumen Toserba Yogya Gatot Subroto Bandung. Metode analisis data dalam penelitian ini menggunakan analisis regresi linear sederhana dengan tujuan untuk mengetahui arah hubungan antara variabel independent (X) dan variabel dependent (Y). Penetapan harga di Toserba Yogya Gatot Subroto Bandung bisa dikatakan cukup baik. Tanggapan responden mengenai harga di Toserba Yogya Gatot Subroto Bandung berada pada kategori cukup. Tanggapan responden mengenai keputusan pembelian di Toserba Yogya Gatot Subroto Bandung berada pada kategori cukup. Data terdistribusi normal dan tidak mengalami heteroskedastisitas. Hasil penelitian ini menunjukkan bahwa terdapat pengaruh secara parsial antara variabel harga terhadap keputusan pembelian. Kata kunci: Harga, Keputusan Pembelian